Geografia histórica ambiental: uma geografia das matas brasileiras - Dias, Celia Regina da Silva (2007)
The object of the present study concerns environmental historical geography. The contribution of geography to this particular field, as well as the debates on the theme of nature/history within a multidisciplinary field and their importance to the understanding of nature reinvention are shown here. In order to address these issues we discussed, in the present study, the Brazilian agricultural and forest model, its epistemic and political foundations, in an attempt to understand the process of replacing woods with new forests, the monocultures of trees. These considerations arise from the object of our study, that is,Brazilian silviculture and the preservation and planting of trees in the Brazilian territory. We have concluded that the replacement of woods with extensive monocultures of trees is due to the necessary capital expansion and accumulation, and that silviculture, that presently involves substantial capital investments, is quite different from the silvicultural activity performed in the XIX century, with clear conservation purposes in the use of natural resources.